Prevalence of Usage Nicotine and its Dependence among Patients with Depression - Unaiza Jawad, Rizwan Farooq, Muhammad Saeed Khan, Fahad Ul Zain, Muhammad Shoaib Irfan, Muazzam Fuaad, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Smoking is common and people with mental disorders are no exception. Few studies have looked at the pervasiveness of usage of tobacco and dependence of nicotine in depressed patients in undeveloped states such as Pakistan. Therefore, in this study, the aim was to determine the prevalence of tobacco use, addiction of nicotine and the inspiration to quit smoking in major depressive disorder affected patients. Study Design: A cross-sectional descriptive study. Place and Duration: In the Department of Psychiatry and Behavioral Sciences, LGH Lahore, Pakistan and Psychiatry Alfalah diagnostic centre, Azhar Medical Plaza Timergara for the duration of six months from August 2021 to January 2022. Methods: The study was held amongst patients with diagnosis of depression form the Department of Psychiatry (outpatient and inpatient). A semi-structured form was used to collect data using and for nicotine use; WHO STEPS tool was used. The Nicotine Dependence was assessed by Fagerstrom Test, Smokeless Tobacco by Modified Fagerstrom and Motivation Assessment were used: Willingness to Quit Ladder was pragmatic for users of nicotine. The data was analyzed and compiled using the SPSS version 20.0. Results: The study comprised 110 subjects (mean age: 36.2 ±9.80 years, 50 men and 60 women) diagnosed with Major Depressive Disorder (mean disease duration: 1.56 ± 2.21 years) were included. 60 of 110 patients (54.5%) used one type or numerous types of tobacco. The patients smoked only tobacco were (n = 38, 63.4%), smokeless tobacco was used by 14 subjects (23.3%) and 13.3% (n = 8) used smokeless and smoked tobacco both. The percentage of smokers of any type of tobacco is greater in men as compared to women (p = 0.029). Among who smokes (n = 38), about fifty percent were heavily addicted 24(63.2%), and 14 (36.8%) were moderately addicted. Almost all (92.8%) of the smoke-less category (n = 14) were highly addicted. Among the combined users, almost all (6/8 = 75%) were heavily addicted to nicotine. A comparatively insignificant proportion (23.3%) of users of nicotine were strongly agreed to stop using any tobacco type. Conclusions: The usage of nicotine prevalence and dependence was supposed to be greater in individuals with depression. In low-resource environments such as Pakistan, the practice of translated and standardized tools of screening can be effectively cast-off to assess the nicotine usage burden in standard practice clinically.